(untitled) (Revista de Ciências Agroveterinárias, 2017)
The factors influencing the final quality of the passion fruit are many, among them the quality of seedlings and the adequate management and farming practices stand out. So, the objective of this work was to evaluate the quality of yellow passion fruit cultivated with seedlings at different ages. For the establishment of the seedlings seeds of the yellow passion fruit cv were utilized. Redondo Amarelo, substrate composed of soil+sand+manure in the ratio of 3:1:1 and plastic bags for up to 8 kg of weight. The experimental design utilized was in randomized blocks (DBC) with five treatments made up of different ages (25, 50, 75, 100 and 125 days, after emergence) with four replications of twelve plants. The variables surveyed were: fresh mass of the fruit (g) longitudinal and transversal diameter of the fruit (mm), fruit shape index, skin thickness (mm), percentage of skin, juice and seed (%), total soluble solids, total titrable acidity and (pH). The use of seedlings aged 100 and 125 days after emergence in yellow passion fruit cultivation showed satisfactory results for all characteristics, deducing feasible to use. The cultivation of yellow passion fruit formed with younger seedlings, compared to other ages obtained a low productivity, lower fruit and less juice yield.